Answer :

We know that,

nth term = Tn = a + (n – 1)d


where,


a = first term


d = common difference


For the above series,



And,





d = 1


Now,


Tn = a + (n – 1)d





Hence, the nth term is


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses